QPI Allows in vitro Drug Screening of Triple Negative Breast Cancer PDX Tumors and Fine Needle Biopsies - Murray, Graeme F.; Turner, Tia H.; Guest, Daniel; Leslie, Kevin A.; Alzubi, Mohammad A.; Radhakrishnan, Senthil K.; Harrell, J. Chuck; Reed, Jason (Frontiers in Physics, 2019)
The development of resistance to initially successful cancer therapies is a major cause of the morbidity and mortality associated with cancer. Identifying evolving resistance at an early stage could inform clinical decision making to adapt therapies before resistant cancer cell phenotypes have become clonally dominant or metastasized. This goal of early detection has prompted heavy investments in liquid biopsy, organoid, and high-throughput screening methodologies. Recently, High-Speed Live-Cell Interferometry (HSLCI), a quantitative phase imaging (QPI) methodology, was shown to predict triple-negative breast cancer (TNBC) patient-derived xenograft (PDX) sensitivity to carboplatin only 40 hours after tumor removal from a mouse. Before HSLCI can be tested in the clinic, it must be adapted for minimally invasive sample acquisition techniques, throughput must be increased to enhance drug screening capacity, and, like any screening method, protocols must be adjusted to reflect drug-specific effects. To overcome these barriers, the system’s hardware was redesigned to increase throughput six-fold and enable the simultaneous screening of multiple therapeutics, and experiments were expanded to include several new classes of drugs. Additionally, the updated system was then incorporated into fine needle biopsy-compatible protocols that were developed for HSLCI and yielded data concordant with recently-published in vivo screens.